Czym jest i dokąd sięga rodzaj (nie)naturalny? - Wojdak, Piotr (Slavia Occidentalis, 2016)
The article presents considerations concerning the essence and the scope of the concept of the natural gender of nouns. The author advocates its grammatical categorisation – instead of the semantic categorisation dominating in the literature. This means that the superior category in natural gender should be grammatical gender (hence the proposed compound term: natural grammatical gender), and not a semantic feature. In a simple (prototypical) categorisation, natural gender pertains to masculine nouns with male meaning and feminine nouns with female meaning. The article identifies five types of possible extension of this concept: 1. the isolation of the neuter natural gender; 2. the attribution of natural gender to nouns with inconsistent semantics of sex; 3. the recognition of the natural gender which is incompatible with grammatical gender (this extension is only possible when natural gender is treated as a semantic feature); 4. the analysis of all nouns that denote sexual beings with regard to natural gender; 5. the isolation of subcategories of natural masculine nouns (natural genders of the second degree). Complimentary to the narrow understanding of natural gender, the author proposes to use an antonymous term – “unnatural gender” to designate such kind of grammatical gender of personal (or animate) nouns that is not in compliance with their semantic feature of sex (e.g., CHŁOPISKO [A CHAP], BABSZTYL [A HAG]).